A SAFE HARBOUR: A PREDETERMINED MARGIN METHOD TO REDUCE TRANSFER PRICING COMPLIANCE BURDEN - Maria R.U.D. Tambunan (Faculty of Law, Universitas Gadjah Mada, 2021)
Abstract The safe harbour provision was unpopular since the beginning of transfer pricing (TP) implementation in Indonesia, even though this provision has been well-known in several countries. Indonesia’s existing safe harbour provision has solely governed the threshold on TP documentation obligation that could not offer certainty about tax audit treatment. The TP threshold refers to the total transaction volume per fiscal year with an affiliation that allows taxpayers to get relief from submitting TP documentation. A deemed profit also applies to a certain manufacture contract. With current provisions, the TP burden of taxpayers and tax administration could not reduce because no certainty on the tax audit exemption with the existence of the threshold provision. Therefore, it needs to improve the safe harbour rule to enhance the certainty manufacturer and reduce the administrative burden. Abstrak Ketentuan safe harbour sebagai bagian dari ketentuan transfer pricing (TP) belum populer di Indonesia, meskipun ketentuan tersebut cukup popular di berbagai negara. Ketentuan yang ada di Indonesia saat ini hanya terkait penentuan ambang batas kewajiban pendokumentasian TP yang belum memberikan kepastian hukum terkait pemeriksaan pajak. Ambang batas tersebut diperhitungkan berdasarkan total volume transaksi dengan afiliasi selama satu tahun fiskal yang memungkinkan wajib pajak mendapatkan keringanan dari penyerahan dokumentasi TP. Selain itu, terdapat ketentuan deemed profit (perkiraan keuntungan) bagi perusahaan kontrak manufaktur tertentu. Ketentuan saat ini belum mampu mengurangi kewajiban administratif TP bagi wajib pajak dan otoritas pajak karena tidak adanya kepastian bahwa wajib pajak yang tidak memenuhi ambang batas. Oleh karena itu, diperlukan penyempurnaan atas ketentuan yang berlaku saat ini untuk menciptakan ketentuan safe harbour yang memberikan kepastian dan pengurangan beban administrasi.